A stepping stone to the "West": Academic adaptation of international students from post-Soviet countries in Hungary. (July 2022) - Yerken, Aigerim; Nguyen Luu, Lan Anh
Abstract: The study aimed to investigate the academic adaptation experiences of international students from post-Soviet countries in Hungary. Semi-structured interviews were conducted with 42 international students from Kazakhstan, Azerbaijan, Georgia, and Moldova, studying at an institute of higher education in Hungary. We used reflexive thematic analysis to explore the adaptation experiences of the international students and to analyze a relatively large dataset. Three themes were generated: (1) From the post-Soviet to the "Western world"; (2) Comparison and contrast; and (3) Managing in an unknown academic environment. The results show that push-pull factors affected the international students' decision to study abroad. International students consider Hungary as a "transit" country — an "affordable stepping stone" from which to look for future educational or job opportunities in other Western countries. Our findings also emphasize the importance of cultural distance in the institutional context of post-Soviet countries and Hungary.